Love and Interest Rates: Property Law by Eugenie Grandet - Cabán Vales, Pedro (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2022)
Acquisition of goods and indebtedness are major subjects in Eugenie Grandet, a novel by Honoré de Balzac. Civil and Business Law Institutions such as matrimonial property regime, inheritance, loans and bankruptcy are major subjects of the storyline. That is the reason why a close look into such legal terms is vital to a full understanding of such work of literature.
Keywords: Law; literature; Balzac; Eugenie Grandet; Property Law